The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/ncomms12392
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Corrigendum: Beta 1-integrin–c-Met cooperation reveals an inside-in survival signalling on autophagy-related endomembranes

Abstract: The original version of this Article contained an error in the spelling of the author Luisa Robbez-Masson, which was incorrectly given as Luisa Robert-Masson. This has now been corrected in both the PDF and HTML versions of the Article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 1 publication
2
24
0
Order By: Relevance
“…Events such as c-Met gene mutation, overexpression, and amplification may be closely related to aberrant activation of HGF/c-Met signaling in human cancers (Barrow-Mcgee et al, 2016;Bahrami et al, 2017). Increasing preclinical evidence has allowed for development of specific molecular inhibitors, including anti-c-Met monoclonal antibodies and small molecule tyrosine kinase inhibitors (TKIs).…”
Section: Mirna Lncrna-based Therapeutics In C-met-related Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Events such as c-Met gene mutation, overexpression, and amplification may be closely related to aberrant activation of HGF/c-Met signaling in human cancers (Barrow-Mcgee et al, 2016;Bahrami et al, 2017). Increasing preclinical evidence has allowed for development of specific molecular inhibitors, including anti-c-Met monoclonal antibodies and small molecule tyrosine kinase inhibitors (TKIs).…”
Section: Mirna Lncrna-based Therapeutics In C-met-related Cancermentioning
confidence: 99%
“…Amplification of c-Met was detected in patients with advanced solid cancers (Jardim et al, 2014). Furthermore, mutations, overexpression, or amplification of the MET gene in some tumor types resulted in aberrant HGF/c-Met axis activity, which induced cell motility and proliferation, promoted tumor development, and led to resistance to radiotherapy and targeted drug therapy in multiple cancers (Minuti et al, 2012;Barrow-Mcgee et al, 2016;Bahrami et al, 2017). Clinical trials of drug monotherapies targeted to c-Met have shown promising outcomes against multiple cancer types (Spigel et al, 2013;Solomon et al, 2014;Kogita et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In many cancers, Met is mostly overexpressed rather than mutated. We have shown that, in several cancer cell lines expressing endogenous nonmutated Met, HGF stimulation triggers a rapid internalization of Met (Kermorgant et al, 2003 , 2004 ; Kermorgant and Parker, 2008 ; Ménard et al, 2014 ; Barrow-McGee et al, 2016 ). Interestingly, Met remains bound to HGF and activated on endosomes.…”
Section: The Receptor Tyrosine Kinase Metmentioning
confidence: 99%
“…Furthermore, the optimal activation by Met of signals, such as ERK1/2, STAT3, and Rac1 requires an intact endocytosis machinery (Kermorgant et al, 2004 ). Met was shown to signal in several types of endosomes: the early endosome, the late endosome, and a novel endosome decorated by LC3 that we named “Autophagy Related Endomembrane, ARE” (Kermorgant et al, 2004 ; Kermorgant and Parker, 2008 ; Joffre et al, 2011 ; Ménard et al, 2014 ; Barrow-McGee et al, 2016 ).…”
Section: The Receptor Tyrosine Kinase Metmentioning
confidence: 99%
See 1 more Smart Citation